Practice of standard Cross Infection Protocol in Private Dental Clinics of Khyber Pakhtunkhwa, Pakistan: A cross-sectional study - Maqbool, Hassan; Sajid, Khadija; Rizwan, Zarnab (Journal of Rawalpindi Medical College, 2022)
Background: Infection control, which is considered to be the backbone of dentistry, has become a particularly essential piece of dental training because both the dentists and patients are at an expanded danger of cross-contamination. Dental clinical settings represent a high organic hazard of spreading a wide scope of microorganisms. The objective of this study is to gather information of different dentists regarding their practice of standard cross infection protocols and how can they improve the same in their private practices. Materials and Methods: This cross-sectional study was conducted in dental clinics of Khyber Pakhtunkhwa, KPK from January 2020 to July 2020 by distributing a questionnaire among dentists. It was a pre-designed questionnaire that was circulated in Google forms through Whatsapp and emails. The questionnaire was divided into 2 sections. Data was compiled and statistical tests were applied using the Statistical Package for Social Sciences SPSS® ver.23.0 Results: Regarding cross infection control measures, maximum dentists seem to have knowledge of cross infection control techniques. A significant difference was found (p= 0.05) between male & female dentists in disposing dental waste from clinical set up properly. A significant difference was also found between male & female dentists about rubber dam isolation (p=0.02). Conclusion: The result of this study showed that practice of dentists in KPK is not up to standard protocols of cross infection control. In this way, the need of great importance is to authorize and execute better proportions of infection control to improve dental practice in KPK. Key words: Infection control, Dental practice, Sterilization